Struktur komunitas makroinvertebrata bentos di hutan Selorejo Dau Malang: Structure of benthic macroinvertebrate community at the Selorejo forest in Dau, Malang - Noviza, Evi Noris; Zayadi, Hasan; Prasetya, Hamdani Dwi (Jurnal SAINS ALAMI (Known Nature), 2024)
This study aims to determine the community structure of benthic macroinvertebrates in the Selorejo forest. That it is hoped it can be used as a basis for evaluating water quality of river in the Selorejo forest, Dau District, Malang. Macroinvertebrate benthic samples were taken at three different stations, with three replications at each station, namely protection forest (station 1), production forest (station 2), and tourism forest (station 3). Samples were taken using a surfer's net. The samples obtained were then analyzed for wealth taxa, INP (Importance Value Index), and their diversity index which includes diversity index, uniformity index, and dominance index. In this study, 10 species were obtained from three stations; Ilyocoris sp., Stenacron interpunctatum, Hydrochara sp., Bradybaena similiaris, Hydropsyche bronta, Diphetor hageni, Dugesia tigrina, Similium vittatum, Tabanus sp. and Perlesta sp. Species with the highest tolerance level were found at stations where human activity often occurred, namely in tourist forests based on the Shannon-Wiener diversity index.  Keywords: Selorejo forest, benthic macroinvertebrates, community structure. ABSTRAK Penelitian ini bertujuan untuk mengetahui struktur komunitas makroinvertebrata bentos di hutan Selorejo, sehingga diharapkan nantinya dapat dijadikan dasar evaluasi kualitas air di sungai hutan Selorejo, Kecamatan Dau, Malang. Sampel makroinvertebrata bentos diambil pada tiga stasiun berbeda, dengan tiga kali ulangan pada masing-masing stasiun yaitu hutan lindung (stasiun 1), hutan produksi (stasiun 2), hutan wisata (stasiun 3). Sampel diambil dengan menggunakan jaring surber. Sampel yang sudah didapatkan selanjutnya di identifikasi untuk dianalisis kekayaan taksa/taxa richness, INP (Indeks Nilai Penting), dan indeks diversitasnya meliputi indeks keanekaragaman, indeks keseragaman, dan indeks dominansi. Pada penelitian ini didapatkan 10 speies dari ketiga stasiun yaitu Ilyocoris sp., Stenacron interpunctatum, Hydrochara sp., Bradybaena similiaris, Hydropsyche bronta, Diphetor hageni, Dugesia tigrina, Similium vittatum, Tabanus sp. dan Perlesta sp. Spesies dengan tingkat toleransi tinggi paling banyak ditemukan pada stasiun yang sering terjadi aktivitas manusia yaitu pada hutan wisata berdasarkan indeks diversitas Shannon-wiener.  Kata kunci : Hutan Selorejo, Makroinvertebrata bentos, struktur komunitas.